Functional resting state connectivity is differentially associated with IL-6 and TNF-α in depression and in healthy controls - Schmitz, Christian N.; Sammer, Gebhard; Neumann, Elena; Blecker, Carlo; Gründer, Gerhard; Adolphi, Hana; Lamadé, Eva; Pedraz Petrozzi, Bruno (Scientific reports, 2025)
Inflammatory processes have been implicated in the pathophysiology of depression. In human studies, inflammation has been shown to act as a critical disease modifier, promoting susceptibility to depression and modulating specific endophenotypes of depression. However, there is scant documentation of how inflammatory processes are associated with neural activity in patients with depression. We therefore tested the hypothesis that the peripheral inflammation markers IL-6 and TNF-α correlate with neural resting state network functional connectivity in depression using functional magnetic resonance imaging (fMRI) and compared it with healthy controls. We used fMRI to investigate the functional connectivity (FC) of the resting state Default Mode Network (DMN) and Salience/Ventral Attention Network (SAL) and their association with the peripheral inflammation markers IL-6 and TNF-α in 25 patients with depression and compared it to 24 healthy subjects. Results of this imaging study revealed that both DMN and SAL resting state networks are differentially associated with distinct immunological pathways depending on whether a person has a depressive phenotype or is healthy. While the DMN FC correlated with the concentration of the cytokine IL-6 in healthy subjects, SAL FC’s connectivity correlated with the cytokine TNF-α's concentration. This study highlights the importance of peripheral inflammatory processes in depression and suggests a modulatory effect on neural resting state networks depending on the state of depression.
Gesehen am 15.01.2026